2010
DOI: 10.1016/j.vaccine.2010.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic defects in B cell response to seasonal influenza vaccination in elderly humans

Abstract: We have evaluated the serum response to seasonal influenza vaccination in subjects of different ages and associated this with the specific B cell response to the vaccine in vitro. Although the serum response has previously been shown to decrease with age, this has largely been associated to decreased T cell functions. Our results show that in response to the vaccine, the specific response of B cells in vitro, as measured by AID (activation-induced cytidine deaminase), the in vivo serum HI (hemagglutination inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
163
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(185 citation statements)
references
References 48 publications
18
163
4
Order By: Relevance
“…The central role of B cells in the vaccination response has already been shown by Frasca et al, who demonstrated that intrinsic B cell defects in the elderly contribute to reduced antibody responses to influenza vaccine [32].…”
Section: Discussionmentioning
confidence: 75%
“…The central role of B cells in the vaccination response has already been shown by Frasca et al, who demonstrated that intrinsic B cell defects in the elderly contribute to reduced antibody responses to influenza vaccine [32].…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, the inability of old individuals to effectively respond to vaccines results in less effective immunizations against viruses and bacteria, thus increasing the risk of infections and diseases (Miller and Cancro 2007;Cancro et al 2009;Gibson et al 2009;Dunn-Walters and Ademokun 2010;Frasca and Blomberg 2011). Indeed, it is well documented that the immune response to vaccination declines with age, although the reasons for this are poorly understood (Kumar and Burns 2008;Frasca et al 2010;McElhaney et al 2012). It is also known that in the elderly, there is an impairment of both innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that elderly people show changes in B cell number, low levels of antibody production, and poor responses to recall antigens, and a collapse in B cell receptor repertoire diversity correlated with poor health status and the impairment of antibody response (Miller and Cancro 2007;Kumar and Burns 2008;Cancro et al 2009;Gibson et al 2009;DunnWalters and Ademokun 2010;Frasca et al 2010;Frasca and Blomberg 2011;McElhaney et al 2012). Lower numbers and percentages of B cells also form part of the cluster of immune parameters collectively known as the "Immune Risk Profile" associated with 2-, 4-, and 6-year mortality of the very elderly in the Swedish OCTO/ NONA longitudinal studies (Pawelec et al 2005).…”
Section: Cd24mentioning
confidence: 99%
“…However, in vitro stimulation of human peripheral blood B cells by anti-CD40 and IL-4 induces a lower production of IgG from elderly donors, correlated to a reduction of the transcription factor E47 and AID in old people (Frasca et al, 2008). Moreover the same authors have recently demonstrated that the level of AID in response to polyclonal stimulation by CpG can predict the size of the response to influenza vaccination (Frasca et al, 2010a).…”
Section: B Lymphocytesmentioning
confidence: 99%